Antioxidant capacity of essential oil spice extracts versus ground spices and addition of antioxidants in Bulgarian type dry-fermented sausages - Dragoev, Stefan G.; Balev, Dessislav K.; St. Nenov, Nenko; Vassilev, Kiril P.; Vlahova-Vangelova, Dessislava B. (European journal of lipid science and technology, 2016)
The dry‐fermented sausages are under high risk of microbial cross‐contamination and physical impurities come from ground spices because they are not subjected to heat treatment. So, the objective of this study was to investigate the replacement of 3 g/kg ground black pepper (Piper nigrum L.), and cumin (Cuminum cyminum) with their aliquots of tetrafluoroethane extracts on oxidation stability in dry‐fermented sausages. The influence of 0.2 g/kg added antioxidants: Dihydroquercetin from Siberian larch (Larix sibirica Ledeb), rosemary (Rosmarinus officinalis L.) extract, or butylated hydroxytoluene on the antioxidant activity was studied too. For this purpose the acid value (AV), conjugated dienes and trienes, peroxide value (POV), TBARS, and fatty acid composition of Bulgarian‐type dry‐fermented sausages sudjuk Sadowski, were determined. The replacement of ground black pepper and cumin with tetrafluoroethane essential oil extracts in sudjuk effectively decrease the rate of lipolysis and lipid oxidation during processing and 30 days storage at 0–4°C. In comparison with control samples the AV was reduced by more than 38%, POV with 50.8%, conjugated dienes with 8.82%, conjugated trienes with 39.3%, and TBARS with approximately 39%. A strong linear correlation between TBARS and POV (R2 > 0.94); AV and POV (R2 > 0.89), and AV and TBARS (R2 > 0.83) was obtained. Practical applications: The black pepper and cumin tetrafluoroethane essential oil extracts or addition of 0.02% of natural antioxidants, such as dihydroquercetin and rosemary powder extract can be used in the composition of the Bulgarian type dry‐fermented sausages such as sudjuk. They show strong antioxidant capacity with beneficial effect on lipolytical changes and lipid oxidation stability during 30 days vacuum storage at 0–4°C. In general, results suggest that black pepper and cumin tetrafluoroethane essential oil extracts with the combination of dihydroquercetin or rosemary powder extract can be successfully applied to protect dry‐fermented sausages from lipid oxidation. Sample C, dry‐fermented sausages prepared with ground spices; sample E, dry‐fermented sausages prepared with tetrafluoroethane spices extracts; sample B, dry‐fermented sausages prepared with ground spices and 0.2 g/kg BHT; sample R, dry‐fermented sausages prepared with ground spices and 0.2 g/kg rosemary extract; sample T, dry‐fermented sausages prepared with ground spices and 0.2 g/kg dihydroquercetin. Sample C, dry‐fermented sausages prepared with ground spices; sample E, dry‐fermented sausages prepared with tetrafluoroethane spices extracts; sample B, dry‐fermented sausages prepared with ground spices and 0.2 g/kg BHT; sample R, dry‐fermented sausages prepared with ground spices and 0.2 g/kg rosemary extract; sample T, dry‐fermented sausages prepared with ground spices and 0.2 g/kg dihydroquercetin.